Legionella pneumophila Strain 130b Evades Macrophage Cell Death Independent of the Effector SidF in the Absence of Flagellin - Speir, Mary; Vogrin, Adam; Seidi, Azadeh; Abraham, Gilu; Hunot, Stéphane; Han, Qingqing; Dorn, Gerald W.; Masters, Seth L.; Flavell, Richard A.; Vince, James E.; Naderer, Thomas (Frontiers in Cellular and Infection Microbiology, 2017)
The human pathogen Legionella pneumophila must evade host cell death signaling to enable replication in lung macrophages and to cause disease. After bacterial growth, however, L. pneumophila is thought to induce apoptosis during egress from macrophages. The bacterial effector protein, SidF, has been shown to control host cell survival and death by inhibiting pro-apoptotic BNIP3 and BCL-RAMBO signaling. Using live-cell imaging to follow the L. pneumophila-macrophage interaction, we now demonstrate that L. pneumophila evades host cell apoptosis independent of SidF. In the absence of SidF, L. pneumophila was able to replicate, cause loss of mitochondria membrane potential, kill macrophages and establish infections in lungs of mice. Consistent with this, deletion of BNIP3 and BCL-RAMBO did not affect intracellular L. pneumophila replication, macrophage death rates, and in vivo bacterial virulence. Abrogating mitochondrial cell death by genetic deletion of the effectors of intrinsic apoptosis, BAX and BAK, or the regulator of mitochondrial permeability transition pore formation, cyclophilin-D, did not affect bacterial growth or the initial killing of macrophages. Loss of BAX and BAK only marginally limited the ability of L. pneumophila to efficiently kill all macrophages over extended periods. L. pneumophila induced killing of macrophages was delayed in the absence of capsase-11 mediated pyroptosis. Together, our data demonstrate that L. pneumophila evades host cell death responses independently of SidF during replication and can induce pyroptosis to kill macrophages in a timely manner.